Poliítica e resistências protocolares: torções e reforços no diagrama da sociedade de controle - Rivero, Facundo Guerra (2006)
This study investigates contemporary manifestations of resistance. The starting point for such study is the flow of information - the Internet is deemed herein as the model diagram and a fundamentally important mechanism, entwined in power relations in the control society. Resistance and control are inevitably associated and therefore operate through this mechanism. Hence, this study investigates not only contemporary control, which operates through mechanisms of social subjection and mechanistic servitude, where men are components of a machine, controlled and directed by a superior unit, found in this study to be in protocols, operated in turn by molar and molecular lines that seal the Internet s control grid, but escape lines are also contemplated, represented by hackers, who assemble as war machines and throw themselves against the State apparatus and the global war machines in search of freedom